(Dis)embodying Myths in Ancien Régime Opera : Multidisciplinary Perspectives - Forment, Bruno (Book collections on Project MUSE., 2012)
Throughout the Ancien Regime, mythology played a vital role in opera, defining such epoch-making works as Claudio Monteverdi's 'La favola d'Orfeo' (1607) and Christoph Gluck's 'Iphigenie en Tauride' (1779). The operatic presence of the Greco-Roman gods and heroes was anything but unambiguous or unproblematic, however. This book highlights myth's chameleonic life in the Italian 'dramma per musica' and French 'tragedie en musique' of the seventeenth and eighteenth centuries.